A new conceptual method for project evaluation - Hashemi, Seyed Zabihollah; Sharifi, Azita Sherej; Charrakh, Maryam (2013)
To ensure a project's success, a tool is needed to maintain performance. A tool which will cover all aspects of the project and provides a wider decision making scope for the managers. It is very difficult to find such a comprehensive and complete method which has high accuracy and offer practical information in evaluating the method of development and performance of a given project. However, research has shown that without a prospective strategic outlook on project organization, the chance of success of a given project is diminished. This article is aimed to show the traditional methods and to offer an alternative method using a modified version of the balanced evaluation approach ( i.e. BSC tool) and the acquired value method (EVM) to evaluate project performance. This modified tool is termed as the project balance evaluation approach (PBC).
Keywords: Project management -- Evaluation